Corporate Social Responsibility and NGO Activity in China and India: A Comparative Study of Corporate Website Reporting - Jones, Daniel F. (2009)
It is well recognised that CSR is not a uniformly homogenous concept. Rather, it varies between countries and supra-national regions. This work compares the salience and role of NGOs as agents for influencing the uptake and focus of CSR in China and India. Four hypotheses are addressed: i) Companies in India are more likely to engage with their stakeholders than are companies in China, ii) NGOs act as more salient stakeholders in India than in China, and thus are more capable of influencing CSR engagement, iii) Differences in the institutional environments cause different patterns of CSR to emerge in China and India, and iv) These institutional differences also define the difference in NGO salience.